Leading and managing change in the age of disruption and artificial intelligence - Donald, Mathew (Emerald Publishing Limited, 2019)
In a global age of disruption, future organisational change is not avoidable. Organisational effects will be immediate and transformational across companies, and due consideration and preparation ahead of these changes may be paramount for the survival of organisations and their leaders of tomorrow. Leading and Managing Change in the Age of Disruption and Artificial Intelligence modernises the topics of management, leadership, and organisational change to inform those leading and managing organisations into the future. The book covers modern disruptions ranging from Trump and other geo-political changes, to Brexit, new currencies, trade wars, and even knowledge mobility. It also considers the broad scope of potential impacts posed by artificial intelligence. With insights and strategies that the modern manager of the future can implement in their daily work, this book provides critical thinking that will future proof organisations with practical models. It will interest and inform managers and leaders across small and large organisations and will also prove useful and thought-provoking to those studying in business related disciplines such as management, leadership, and organisational change.